2008
DOI: 10.1016/s1474-4422(08)70019-x
|View full text |Cite
|
Sign up to set email alerts
|

Current and future uses of neuroimaging for cognitively impaired patients

Abstract: Correspondence to: Gary Small, Semel Institute, Suite 88-201,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 128 publications
(122 reference statements)
0
109
0
1
Order By: Relevance
“…The most apparent aging-related brain change is an atrophy resulting from synaptic and neuronal loss. This atrophy is larger in individuals with dementia and often shows a regional variation depending on the form of dementia that the patient suffers (Small et al, 2008). However, there are also areas in which anatomical changes do not distinguish between these disorders.…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most apparent aging-related brain change is an atrophy resulting from synaptic and neuronal loss. This atrophy is larger in individuals with dementia and often shows a regional variation depending on the form of dementia that the patient suffers (Small et al, 2008). However, there are also areas in which anatomical changes do not distinguish between these disorders.…”
Section: Neuroimagingmentioning
confidence: 99%
“…(Pakrasi and O'Brien, 2005;Silverman et al, 2001). These alterations in AD have been shown to be distinctive from controls and from other types of dementia and to correlate with cognitive impairment in MCI patients (Small et al, 2008). In terms of diagnostic accuracy, PET assessment of glucose metabolism has been found to have high sensitivity (94%) but low specificity (73-78%) ).…”
Section: Functional Mri (Fmri)mentioning
confidence: 99%
“…1 A thorough understanding of the influence of age on glucose metabolism is important to ensure a better distinction between normal and pathologic brain changes associated with the process of human aging. The first wave of PET studies designed to investigate normal brain aging was during the 1980s and was characterized by an overall agreement that there is no glucose hypometabolism in individuals without dementia.…”
mentioning
confidence: 99%
“…5 Several studies using region-of-interest (ROI) and voxel-based analyses have reported reduced volumes in the hippocampus, parahippocampal gyrus, cingulate and other brain regions in patients with mild cognitive impairment (MCI) and AD. 2,[6][7][8] The spatial pattern of brain atrophy in MCI is complex and highly variable and does not always progress in a linear manner. Characterizing these inter-individual variations in the manifestation of these diseases through the development of biomarkers poses even greater challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing these inter-individual variations in the manifestation of these diseases through the development of biomarkers poses even greater challenges. 8,9 There is strong evidence that the cerebellum not only modulates important motor functions, but also plays a significant role in the operation of cognitive functions, emotional processing, and behavior. 10,11 From this perspective, the cerebellum exerts a regulatory function that enhances and supplements other brain functions, throughout direct and indirect circuits.…”
Section: Introductionmentioning
confidence: 99%